Tuning the Cytokine Responses: An Update on Interleukin (IL)-4 and IL-13 Receptor Complexes - Junttila, Ilkka S. (Frontiers in Immunology, 2018)
Interleukin(IL)-4 and IL-13 are related cytokines that regulate many aspects of allergic inflammation. They play important roles in regulating the responses of lymphocytes, myeloid cells and non-hematopoietic cells. In T-cells IL-4 induces the differentiation of naïve CD4 T cells into Th2 cells, in B cells IL-4 drives the immunoglobulin(Ig) class switch to IgG1 and IgE, and in macrophages IL-4 and IL-13 induce alternative macrophage activation. This review gives a short insight into the functional formation of these cytokine receptors. I will discuss both the binding kinetics of ligand/receptor interactions as well as the expression of the receptor chains for these cytokines in various cell types; both of which are crucial factors in explaining the efficiency by which these cytokines induce intracellular signaling and gene expression. Work initiated in part by William (Bill) E. Paul on IL-4 some thirty years ago has now grown into a major building block of our current understanding of basic immunology and the immune response. This knowledge on IL-4 has growing clinical importance as therapeutic approaches targeting the cytokine and its signal transduction are becoming a part of the clinical practice in treating allergic diseases. Just by reading the reference list of this short review, one can appreciate the enormous input Bill has had on shaping our understanding of the pathophysiology of allergic inflammation and in particular the role of IL-4 in this process.